2015
DOI: 10.1007/s00167-015-3660-2
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of postural control in patients with mechanical ankle instability after lateral ankle ligaments reconstruction

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…In the present study, time to peak torque for dorsiflexion and eversion was significantly increased in the affected ankles of the MBP group compared with those of normal control groups. after MBP [12], and Konradsen et al demonstrated that delayed muscle reaction time was not related to ligament injury or mechanical instability [39]. Given that the results of the present study were consistent with those of previous studies, we believe that proprioception and neuromuscular training should be considered as a method to improve muscular recruitment time in dorsiflexion and eversion [40,41].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, time to peak torque for dorsiflexion and eversion was significantly increased in the affected ankles of the MBP group compared with those of normal control groups. after MBP [12], and Konradsen et al demonstrated that delayed muscle reaction time was not related to ligament injury or mechanical instability [39]. Given that the results of the present study were consistent with those of previous studies, we believe that proprioception and neuromuscular training should be considered as a method to improve muscular recruitment time in dorsiflexion and eversion [40,41].…”
Section: Discussionsupporting
confidence: 89%
“…This study had several limitations. First, there is the possibility that visual compensation may directly affect postural stability, as reported by Li et al [12]. However, the control screen was covered to reduce any bias in the postural stability tests in the present study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Current literature suggests that a certain degree of mechanical instability cannot be compensated by functional training but may instead require mechanical stabilization [ 8 , 23 ]. Whether an undetermined severity of mechanical insufficiency inevitably leads to an additional perception of instability, according to the model of Hiller et al [ 24 ], remains unclear in current literature [ 4 , 25 ].…”
Section: Introductionmentioning
confidence: 99%